SEBUAH KAJIAN CULTURAL CRIMINOLOGY ATAS MOSHING DI DALAM KONSER UNDERGROUND - Muhamad Robbyansyah (Jurnal Kriminologi Indonesia, 2011)
This minithesis discussed about moshing phenomenon in an underground music concert as a considerable study about criminalization of popular culture’s product in society, and how to deconstruct the meaning of it. This study has been done in qualitative approach with researcher being a medium for data references to get the ”first person” view for seeing the true meaning of moshing in an underground community. They are suffered with culture constructiont made by the dominant culture above and doing deconstruction of it as a reaction of dominant culture’s construct.